2017
DOI: 10.1128/aac.01009-17
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Drug Penetration of Echinocandin Antifungals at the Site of Infection in an Intra-abdominal Abscess Model

Abstract: Intra-abdominal candidiasis (IAC) is a prominent invasive fungal infection associated with high mortality. Prompt antifungal therapy and source control are crucial for successful treatment. Echinocandin antifungal drugs are first-line agents; however, their clinical effectiveness is highly variable, with known potential for breakthrough resistance, and little is known about drug exposure at the site of infection. Using matrix-assisted desorption ionization mass spectrometry imaging technology, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 42 publications
2
79
0
Order By: Relevance
“…Our data suggest that caspofungin MPCs exceed clinically achievable levels at these sites, whereas anidulafungin and micafungin MPCs are lower. New technology such as matrix-assisted laser desorption/ionization mass spectrometry imaging now allow the visualization of drug disposition within target organs (25). Using a murine model of IAC, we demonstrated that micafungin is quickly distributed into liver and kidney tissue, but the drug concentrates around the outer rim, rather than inside, fungal lesions.…”
Section: Discussionmentioning
confidence: 95%
“…Our data suggest that caspofungin MPCs exceed clinically achievable levels at these sites, whereas anidulafungin and micafungin MPCs are lower. New technology such as matrix-assisted laser desorption/ionization mass spectrometry imaging now allow the visualization of drug disposition within target organs (25). Using a murine model of IAC, we demonstrated that micafungin is quickly distributed into liver and kidney tissue, but the drug concentrates around the outer rim, rather than inside, fungal lesions.…”
Section: Discussionmentioning
confidence: 95%
“…The methodology is tremendously powerful since it can be applied to any small molecule drug used in any disease state. Indeed, we have recently quantified an antifungal drug candidate in a mouse model of abdominal candidiasis 14 . Differential drug partitioning into heterogeneous tumor compartments (including necrotic cores) is a primary concern in the treatment of cancer, and a critical area of research in cancer drug discovery 15 .…”
Section: Discussionmentioning
confidence: 99%
“…FKS mutations that impart echinocandin resistance has been reported to also impact rezafungin MICs, although not in all isolates. Broad cross-resistance was seen between rezafungin, caspofungin, and anidulafungin, although rezafungin's "front-loaded" dosing regimen utilized in studies is suggested to lower development of resistance [16]. In vitro studies have also found rezafungin to have potent activity against C. auris, superior to both caspofungin and micafungin [17].…”
Section: Rezafunginmentioning
confidence: 99%